ETHNOBOTANY OF USEFUL TREES IN AGROFORESTRY SYSTEMS IN THE SIERRA DE ZONGOLICA, VERACRUZ, MEXICO - Miguel Ángel Vega Ortega; Sergio Ignacio Gallardo Yobal; Adolfo De Jesús Rebolledo Morales; Claudia Ivet Contreras Hernández (Tropical and Subtropical Agroecosystems)
Background: traditional ecological knowledge generated by different human groups is manifested in the various forms of appropriation of nature, particularly by intervening in the growth processes of plant species to take advantage of them and maintain them in the long term. The sierra of Zongolica is one of the most important indigenous areas in Mexico, where the use of forest resources is part of their livelihoods. There is evidence that in this region trees are used as raw material for furniture, construction, food, charcoal and firewood. Objective: to learn about the diversity, main uses and importance of multipurpose trees within agroforestry systems in the Sierra de Zongolica, Veracruz. Methodology: 74 semi-structured interviews and direct observations were conducted on the land of the interviewees and analyzed using a mixed approach, through a social network analysis to determine the main uses of the trees. Results: A total of 79 species of useful trees were recorded, belonging to 41 taxonomic families, of which the Fabaceae family was the most abundant with 4 species recorded. Sixty-two genera were found, of which the most abundant was the Quercus genus. Ninety-five percent of the informants were men around 50 years of age, demonstrating that they are the ones in charge of the productive activities and that they are the ones with the knowledge about the use and management of the trees. The household is made up of an average of 4 people, which makes it difficult to work in the fields due to the scarcity of family labor, which could jeopardize productive activities because people outside the family must be employed to use and manage the trees. Implications: since wood energy, construction, medicinal and food uses are of vital importance in this work, sustainable management practices should be implemented, such as selective harvesting, replanting and local tree management, so that firewood collection and trade benefit both rural areas and the environment. Conclusions: about 79 useful tree species were identified in Zongolica's agroforestry systems, demonstrating the diversity of natural resources in the region. These species are fundamental to the local economy and environmental conservation, providing firewood, food, medicines and construction materials for local communities. It is crucial to value and protect these forest resources to ensure their continuity and contribute to the sustainability of agroforestry systems in Zongolica.